Rapid and sustainable deep testosterone reduction predicts effective androgen deprivation therapy for metastatic hormone-sensitive prostate cancer - Ze Wang; Haiyang Xiao; Chongliang Zheng; Jian Chen; Qiming Chen; Zhenzhen Chen; Dianzheng Zhang; Luofu Wang; Weihua Lan; Qiuli Liu; Jun Jiang (Scientific Reports)
Abstract The testosterone (TT)/androgen receptor axis plays a crucial role in the initiation and progression of prostate cancer (PCa). We aimed to investigate the predictive value of serum TT levels on metastatic PCa progression. A total of 219 patients with metastatic PCa were included in this study. Analyses performed included Pearson’s correlation test, Wilcoxon rank test, Chi-square test, Cox regression, and Kaplan-Meier analysis. High serum TT levels (> 405 ng/dL) before ADT treatment, deep testosterone reduction (DTR) within the first year of ADT, rapid DTR within 3 months of ADT, and sustained DTR in the first year of ADT are associated with longer CRPC progression-free time. Low serum TT levels before abiraterone treatment are a risk factor for early PSA progression. We constructed a nomogram model based on the DTR within the first year of ADT. Calibration curve and decision curve analyses suggest the model has a high predictive ability for 1-, 1.5-, and 2-year CRPC progression and well clinical utility. Serum TT levels before and during ADT, as well as before abiraterone treatment, can predict metastatic PCa progression. Monitoring serum TT levels throughout the entire course of treatment is crucial for patient follow-up and prognosis.